Evolving Monetary Policy Frameworks in Low-Income and Other Developing Countries : Background Paper. (Policy Papers; Policy Paper, 2015)
This background paper focuses on the experiences of evolving monetary policy frameworks in nine individual countries and three thematic groupings of countries. The country case studies are complemented by analyses of common issues faced by countries in currency unions in the CFA franc zone, selected resource rich countries, and advanced economies and emerging markets during their modernization process of monetary policy regimes. Finally, the background paper also contains a discussion on the benefits of effective communication in conducting monetary policy.